Cerebral MRI findings predict the risk of cognitive impairment in thrombotic thrombocytopenic purpura. (22nd October 2020) - Alwan, Ferras; Mahdi, Dina; Tayabali, Sarrah; Cipolotti, Lisa; Lakey, Grace; Hyare, Harpreet; Scully, Marie
Summary: Thrombotic thrombocytopenic purpura (TTP) is a rare thrombomicroangiopathy caused by deficiency of ADAMTS13. Acute neurological involvement is well described, but its long‐term impact requires evaluation. One‐hundred thirty‐one patients, following an acute TTP event, with severe headache or neurological symptoms had a cerebral MRI. Fifty‐six percent had abnormal imaging, more commonly in patients with neurological symptoms than headaches only (80% vs. 18%, P < 0·0001). In remission, 27% ( n = 35) reported persistent cognitive symptoms: specifically, impaired memory (66%), difficulty concentrating (26%), and word‐finding difficulties not secondary to an acute stroke (26%). Sixty‐five percent also reported depression and 55% reported anxiety, regardless of presenting neurology. The frontal lobe was disproportionally affected in patients with marked intellectual impairment, seen in 67% of patients compared to 19% of patients without intellectual impairment ( P = 0·002). The primary MRI finding in these patients was hyperintense white matter lesions. An abnormal MRI was associated with a lower median verbal IQ (85 vs. 99, P = 0·02) and performance IQ (83 vs. 100, P = 0·02). In conclusion, neurological symptoms are frequently associated with an abnormal cerebral MRI scan, and white matter frontal lobe lesions are particularly significant, leading to marked intellectual impairment. Anxiety and depression were evident in over half of patients, regardless of neurological involvement at presentation.